PENGARUH FASILITAS, KEPERCAYAAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA HOTEL KUSUMA PUTRI HIJAU BENGKULU UTARA - Puja Iza Makhendra; Marliza Ade Fitri (UM. Bengkulu, 2023)
This study aims to determine the effect of facilities, trust and service quality on customer satisfaction at Hotel Kusuma (Case Study on Kusuma Putri Hijau Hotel Employees, North Bengkulu). This type of research uses a quantitative descriptive research method. The population used in this study are consumers who rent or stay at Hotel Kusuma. The number of respondents in this study were 85 people. The data collection method uses a questionnaire and uses analytical techniques using multiple linear regression analysis tests and hypothesis testing, namely the t test and f test. Based on the results of multiple linear regression, the regression equation Y = 1.247 + 0.119X1 + 0.133X2 + 0.106X3 and the results of the t test and f test of this study can be concluded that facilities have a significant effect on customer satisfaction, this is evidenced by the results of the t test showing the value of t_hit> t_table (2.497 > 1.989) and (sig Î± = 0.01 <0.05). This means H_0 is rejected and H_a is accepted. Trust has a significant effect on customer satisfaction, this is evidenced by the results of the t test showing the value of t_hit>t_table (2.437 > 1.989) and (sig Î± = 0.03 <0.05). This means H_0 is rejected and H_a is accepted. Service quality has a significant effect on customer satisfaction, this is evidenced by the results of the t test showing the value of t_hit>t_table (2.510 > 1.989) and (sig Î± = 0.01 <0.01). Facilities (X_1), trust (X2) and service quality (X3) together have a significant effect on customer satisfaction (Y) at the Kusuma Hotel, this is evidenced by the F test showing the value of F_count>F_table, namely (27.554 > 2, 72) and (sig Î± = 0.000 <0.05). This means H_0 is rejected and H_a is accepted. Keywords: facilities, trust and service quality on customer satisfaction.